The Dynamics of Students Religion in Lambung Mangkurat University - Sarbaini, Sarbaini; Husin, Gusti Muhammad Irhamna; Arief, M Ihsanul; Ainah, Noor (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
One of the visible forms of worship is reading, studying and practicing the contents of the Koran. The ability to read the Koran properly that is owned by a person will increase the enthusiasm to deepen it. Thus, fluency and accuracy in reciting the recitation of the Koran is very important for everyone, because it will lead to validity and failure of one's prayers, and also an encouragement to deepen the study of the Koran. This research was conducted at Lambung Mangkurat University in the Teaching and Education Faculty (FKIP), the Faculty of Economics and Business (FEB) and the Faculty of Medicine (FK). The focus of research on students' religious behavior is assessed by their ability to read the Koran by the behavior they display in their daily lives. The method used is a qualitative approach with descriptive analysis techniques. Data were collected using participant observation and dept interview techniques. The interview approach used was structured interviews and free interviews. The research was conducted for two months, (October-November, 2019). Data checking was carried out through focus group discussions. There are three categories that this research produces: first, students who have high quality; second, students who have medium quality; and third, have low quality in reading the Koran. The factors that become the difference in quality are caused by the influence of the family environment, the influence of the previous educational environment, and the influence of the community environment.